I gel versus endotracheal intubation for percutaneous tracheostomies: a randomised study to ascertain amicable approach - Sharma, S. P.; Singh, Anuj (International Surgery Journal, 2021)
Background: Percutaneous tracheostomy or percutaneous dilation tracheostomy (PDT) is an airway management procedure routinely performed in critically ill patients, requiring prolonged ventilation. It is safely performed bedside by anaesthesiologist/intensivist in ICUs. Complications as endotracheal tube (ET) damage, loss of airway due to accidental extubation and piercing of guide wire through ET tube during procedure has led to exploration of safer/effective and viable airway alternatives while performing the procedures. Methods: In this study we randomised 60 patients to group E (ET) and group I (I gel) 30 each and studied ease of carrying out procedure and associated complication rates in both groups. Results: In ET group (group E), 9% of patients suffered with potentially catastrophic complications, e.g. loss of airway, inadequate ventilation of lungs, haemorrhage, airway leak due to ET tube cuff rupture and accidental extubation. In ETT group there was incidence of 18% cuff puncture by guide wire (p=0.025) and 3% accidental tracheal extubation. Group I witnessed lower incidence of haemorrhage (3%) and the incidence of guide wire piercing airway device was nil. Group I also demonstrated better hemodynamic stability attributed to lesser tissue trauma and airway manipulation. Conclusions: This study demonstrates enhanced safety with usage of I gel for PCDT, with less complication, better hemodynamic stability and shorter procedure duration.